2007
DOI: 10.2495/op070151
|View full text |Cite
|
Sign up to set email alerts
|

VTOP — an improved software for design optimization of prestressed concrete beams

Abstract: Optimum tendon layout of prefabricated prestressed concrete beams was an early application of design optimization methodologies. However, most of the approaches found in the literature were not suitable to be implemented in real life bridge engineering. To fill the existing gap research has been conducted in past years by the authors to optimize prefabricated concrete beams formulating the problem in such a way that could be applied directly by bridge designers in beam and slab bridge decks. The software produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 1 publication
0
4
0
1
Order By: Relevance
“…exact methods) and metaheuristic optimization methods. Classical methods attempt to calculate optimal solutions via iterative linear or constrained nonlinear programming techniques in a deterministic way [4][5][6][7][8][9]. As an alternative, metaheuristics with inherent stochastic and evolutionary search features have gained wide attention to leave more room for uncertainty levels in modelling optimization problems with design variables [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…exact methods) and metaheuristic optimization methods. Classical methods attempt to calculate optimal solutions via iterative linear or constrained nonlinear programming techniques in a deterministic way [4][5][6][7][8][9]. As an alternative, metaheuristics with inherent stochastic and evolutionary search features have gained wide attention to leave more room for uncertainty levels in modelling optimization problems with design variables [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the aforementioned research works, there is still limited knowledge on the optimization of prestressed concrete (PC) bridge structures. Hassanain and Loov [24] reviewed research on cost optimization of concrete bridge structures; nevertheless, as Hernandez et al [25] have noted, most approaches for PC bridges found in the literature are not suitable for application in real-life engineering.…”
Section: Introductionmentioning
confidence: 99%
“…PC beam optimization is a classical problem considered many years ago [25]; nevertheless, as Hernandez et al [26] have advised, most approaches for PC bridges found in the literature are not suitable for application in real life engineering. While there is little research on optimization of PC structures [27][28][29][30][31], the literature does include a number of studies on optimizing real-life reinforced concrete (RC) structures [32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%